Enhancing intrinsic motivation and parenting to help underachieving students to perform well in school - Yahaya, Azizi (2004)
This article shares some of the research findings on how intrinsic motivation can be enhanced in areas of self-regulated learning, self-efficacy, locus of control, self –concept, self-esteem, self –worth, cooperative versus competitive learning, moderate risk taking, and the effect of effort and praise. In other words, children who are parented with patience, understanding , affection, and respect will help them to become the best they can be and to accomplish their goals with self- motivation. An array of recommendations from research finds is summed up towards the end of this article. This is thought to be useful and applicable to our context. However, they are by no means the answer to the predicament of the status of achievement in school.